THE INFLUENCE OF GREEN MARKETING AND BRAND IMAGE ON PURCHASE DECISION OF LE MINERALE BOTTLED DRINKING WATER PRODUCTS IN SURABAYA - Galih Syahrul Ilmi; Nuruni Ika Kusuma W (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to analyze the influence of Green Marketing and Brand Image on the purchasing decisions of Le Minerale bottled drinking water. The study uses a sample of 100 respondents, selected based on Ghozali's (2011) theory. The data analysis method used is regression analysis with an R2 value of 0.975130, indicating that the research model can explain 97.51% of the variability in purchasing decisions. The results show that Green Marketing has a significant effect on the purchasing decisions of Le Minerale, indicating that an effective Green Marketing strategy aligns with increased consumer purchasing decisions. Additionally, Brand Image is also found to have a significant influence on purchasing decisions, meaning that an improvement in Le Minerale's Brand Image corresponds to an increase in consumer purchasing decisions. These findings emphasize the importance of green marketing strategies and brand image in influencing consumer purchasing behavior.